A thin-film modeling approach for analysis of carbon capture sorbent-based devices - Flavio D．F． Chuahy; Kellis Kincaid; Kashif Nawaz (Carbon Capture Science & Technology, 2023)
The threat of climate change has driven scientists and engineers to develop new methods reducing carbon emitted as well as capturing CO2 from the atmosphere and other point sources. Carbon capture technology is still in its infancy and requires significant system efficiency improvements before commercial or industrial adoption is not cost prohibitive. Contactor designs must optimize capture efficiency while minimizing pumping losses through this stage, and typical contactors employ a packing material that is wetted with a fluid spray to create a film. The capture efficiency is determined by a complex relationship of operating parameters, contactor geometry, and the chemical kinetics of the CO2 and chosen capture fluid. Due in part to the large parameter space, as well as the physical difficulty of accurately determining capture efficiency, numerical modeling has become an important tool in research and development of contactors for carbon capture. Historically, modeling approaches used for CO2 capture simulations have been too computationally intensive for design work. This work examines the effectiveness of using a thin-film approximation approach to model the reacting fluid, thus avoiding the expensive grid resolution requirements of the volume-of-fluid (VOF) method. Results showed that changes in the reaction model and dissolution constants have a significant impact in the capture efficiency predictions. CO2 capture was largely dictated by the supply of MEA in the film, with capture efficiency reductions as MEA was depleted. Changes in gas temperatures and velocities also had some impact in the CO2 mass transfer. Overall the results validation shows that in a non-flooded contactor, the thin-film approximation is capable of predicting experimental results with sufficient accuracy. Therefore, this model can be used to quickly evaluate contactor designs.